The Effects of Type 2 Diabetes Mellitus on Organ Metabolism and the Immune System - Daryabor, Gholamreza; Atashzar, Mohamad Reza; Kabelitz, Dieter; Meri, Seppo; Kalantar, Kurosh (Frontiers in Immunology, 2020)
Metabolic abnormalities such as dyslipidemia, hyperinsulinemia or insulin resistance and obesity play key roles in the induction and progression of type 2 diabetes mellitus (T2DM). The field of immunometabolism implies a bidirectional link between the immune system and metabolism, in which inflammation plays an essential role in the promotion of metabolic abnormalities (e.g. obesity and T2DM), and metabolic factors, in turn, regulate immune cell functions. Obesity as the main inducer of a systemic low-level inflammation is a main susceptibility factor for T2DM. Obesity-related immune cell infiltration, inflammation and increased oxidative stress promote metabolic impairments in the insulin-sensitive tissues and finally, insulin resistance, organ failure and premature aging occur. Hyperglycemia and the subsequent inflammation are the main causes of micro- and macroangiopathies in the circulatory system. They also promote the gut microbiota dysbiosis, increased intestinal permeability and fatty liver disease. The impaired immune system together with metabolic imbalance also increases the susceptibility of patients to several pathogenic agents such as the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Thus, the need for a proper immunization protocol among such patients is granted. The focus of the current review is to explore metabolic and immunological abnormalities affecting several organs of T2DM patients and explain the mechanisms, whereby diabetic patients become more susceptible to infectious diseases.